2008
DOI: 10.17221/356-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Influence of n-3 and n-6 polyunsaturated fatty acids on sensory characteristics of chicken meat

Abstract: ABSTRACT:The relationship between different levels of n-6 and n-3 PUFA in chicken breast and thigh meat and sensory characteristics of meat was studied. Chickens were fed diets containing 1, 3, 5 or 7 percent of oil made of seeds either of the linseed cultivar Atalante (A) with a high content of α-linolenic acid or of the cultivar Lola (L) with a predominating content of linoleic acid. The meat of chickens fed L showed better sensory characteristics than the meat of birds fed A. If the tissue contained more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 9 publications
(15 reference statements)
5
17
0
Order By: Relevance
“…The fatty acid profile of meat could be altered by adding fish products to the feed for broilers (López-Ferrer et al, 2001a;Cortinas et al, 2004) or vegetable oils (López-Ferrer et al, 2001b;Schneiderova et al, 2007;Zelenka et al, 2008). Similar findings were detected in the present study (Table 3).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The fatty acid profile of meat could be altered by adding fish products to the feed for broilers (López-Ferrer et al, 2001a;Cortinas et al, 2004) or vegetable oils (López-Ferrer et al, 2001b;Schneiderova et al, 2007;Zelenka et al, 2008). Similar findings were detected in the present study (Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…to the diet. It has been shown that the content of n-3 PUFA, particularly of α-linolenic acid (ALA,, in poultry meat can readily be improved by increasing the levels of n-3 PUFA in poultry diets through the incorporation of vegetable oils (López-Ferrer et al, 2001b;Schneiderova et al, 2007;Zelenka et al, 2008) or oily fish by-products (López-Ferrer et al, 2001a;Cortinas et al, 2004). However, some authors reported the unpleasant flavour of fish in the meat of broilers fed 1.5% to 2.5% of FO (Hardin et al, 1964).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar conclusion was also reported by Enser (1999), Webera (2001) or Barroeta (2007). A direct relationship between the spectrum of FAs in fat contained in a diet and the quality of produced poultry meat was confirmed by Zelenka et al (2006Zelenka et al ( , 2008, who tested flaxseed oil, which is of high nutritional value, in their experiments.…”
Section: Resultssupporting
confidence: 82%
“…According to Weber (2001), PUFAs in particular are utilized very effectively from the feed. Similar findings were also reported by Zelenka et al (2006Zelenka et al ( , 2008 who used flaxseed oil. These authors found that diets supplemented with oil enriched with essential fatty acids at favourable ratios will provide poultry meat with an improved nutritional value, which can be declared a functional foodstuff.…”
supporting
confidence: 90%